Auditor quality, audit fees, organizational structure, and risk taking in the US life insurance industry. Issue 2 (8th June 2020) - Huang, Li‐Ying; Lai, Gene C.; Lu, Erin; McNamara, Michael
Abstract: Using a system of simultaneous equations, this study examines the relation among external audit monitoring, in the US life insurance industry. We find insurers with higher leverage risk and surplus risk are more likely to use Big‐4 auditors and to pay higher fees. In return, insurers hiring Big‐4 auditors and paying higher audit fees have lower leverage risk and surplus risk. Second, the results suggest that mutual life insurers have a higher leverage risk and surplus risk than stock life insurers. This evidence is in contrast to that for property–liability insurance companies. Third, we find insurers are less likely to hire Big‐4 auditors and to pay higher audit fees after implementation of the Sarbanes–Oxley Act (SOX). Finally, life insurers with Big‐4 auditors or paying higher audit fees are more likely to take lower risks after the implementation of SOX.